10.52931/icirpe2020 CRITICAL SUCCESS FACTORS DEVELOPMENT OF CLEAN WATER INFRASTRUCTURE AND RURAL SANITATION - Rezi Munizar (International Conference on Industrial Revolution for Polytechnic Education, 2020)
One of the Indonesian government's efforts in the provision of clean water and sanitation infrastructure is the provision of community-based water supply and sanitation (Pamsimas) program. In accordance with the principle of community-based, the active participation of the community becomes the key to success in the implementation of the program. This study analyzes critical success factors (CSFs) in water and sanitation infrastructure development projects through community empowerment approaches. The results showed that there are 10 critical success factors, including government and private intervention in infrastructure (technical and financial) through public private partnership (PPP) and corporate social responsibility (CSR) cooperation schemes; development of competence (skill, knowledge, and job behavior) of member of non-government organization in management of empowerment program activity; strengthening community institutions post-empowerment to trigger community self-reliance in sustainability of empowerment programs; balance between availability and accuracy of allocation of funds through the optimization of project/program management, monitoring and evaluation, independent audits, awareness raising on anti-corruption, and transparency of publicly accessible program financial documents; cultural application of science and technology in all aspects of community development; the formation of a sense of belonging to the community towards the results of development (sense of ownership); strengthening the behavioral commitment of the personnel of the community organization to the established organization; and the stimulation of a responsive approach (demand responsive approach), in the meaning, something that is built must really be needed by the community.